N,N-Bis(4-nitrophenyl)acetamide - Nanaura, Kokichi (International Union of Crystallography, 2013)
In the title compound, C(14)H(11)N(3)O(5), the dihedral angles between the amide group (r.m.s. deviation = 0.0429 Å) and the two benzene rings are 39.66 (6) and 63.04 (7)°. The dihedral angle between the benzene rings is 86.04 (7)°. The benzene rings form dihedral angles of 4.42 (5) and 8.91 (5)° with the adjacent nitro groups. In the crystal, molecules are linked via a pair of C—H⋯O hydrogen bonds, forming inversion dimers, which are linked via a second pair of C—H⋯O hydrogen bonds, forming chains propagating along [100].